1979
DOI: 10.1136/jcp.32.10.979
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reproducibility of subjective grading systems for breast carcinoma.

Abstract: SUMMARY The inter-and intra-observer reproducibility of three grading systems for breast cancer has been analysed: those of the World Health Organisation, of Black, and of Hartveit. In addition, the components forming the basis of these grading systems were analysed separately with regard to reproducibility and interrelationship. In this analysis, degree of differentiation was also included as a parameter.The grading systems of WHO and of Black gave a stratification of the material into three categories of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
3

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(43 citation statements)
references
References 9 publications
1
38
1
3
Order By: Relevance
“…The assessment of histological grade has been criticised because of its subjective nature (Stenkvist et al, 1979). There can also be many problems in using immunohistochemistry as a prognostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of histological grade has been criticised because of its subjective nature (Stenkvist et al, 1979). There can also be many problems in using immunohistochemistry as a prognostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…It is confusing that differentiation is considered together with these factors since it is not known to what extent they contribute independently to the prognostic outcome. This is further underlined in a recent truncated component analysis (17) showing that they do not seem to describe the same biologic phenomenon. In addition, in one study (4) only one expression of differentiation-tubule formation is evaluated, cohesiveness of cell populations of different tumors obtained from the same organ.…”
Section: Key Terms: Breast Cancer Differentiation Morphometrymentioning
confidence: 99%
“…A lot of investigations have been carried out using the nuclear grading system proposed by Black & Speer (1957) or using other nuclear parameters such as nuclear crowding and lobulation (Stenkvist et al, 1979). Their major drawbacks seem to be their lack of reproducibility and their subjectivity (Freedman et al, 1979;Stenkvist et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report (van Bogaert & de Muylder, 1980) we showed that tissue fixation and processing modify nuclear diameters; hence a comparison with cytological data is feasible only after correction by a factor of 1-55. The present study was carried out to verify in tissue sections a possible link between 3 categories of nuclear size and early prognosis.…”
mentioning
confidence: 99%